Persepsi Siswa terhadap Pembelajaran Bahasa Indonesia Berbasis Daring di SMAN 1 Pasuruan - Putikadyanto, Agus Purnomo Ahmad; Efendi, Agik Nur; Romadhon, Sahrul; Amin, Moh. Badruddin; Sefrianah, Nur Aisyah (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The Covid-19 pandemic has had a major impact on all aspects of education around the world. This pandemic shattered the previously established education system. Face-to-face offline learning in schools has been forced to close and disrupt the learning of more than 1.6 billion students worldwide. Learning in droves has turned to using online-based technology, including learning Indonesian in Indonesia. Students are forced to follow these fundamental changes for the sake of the continuity of the learning process. This study attempts to describe students' perceptions of online-based Indonesian language learning in one of the Indonesian schools, SMAN 1 Pasuruan.